Mean Platelet Volume and Platelet Distribution Width as Diagnosis Markers of Acute Perforated Appendicitis in Pediatric Patients - Rahmi Noorhayati; Wahyu Wardhana Wardhana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Symptoms and findings in acute perforated appendicitis (APA) may not always typical in children, becomes difficult to establish the diagnosis preoperatively. Rapid and accurate diagnosis is important to reduce the risk of sepsis and even death. Another biomarkers for diagnosis are needed. This study investigated the diagnostic accuracy of indicators of platelet activation, namely mean platelet volume and platelet distribution width, in children with non perforated acute appendicitis (NPAA) and APA. This retrospective study compared 15 patients with APA (Group I), 15 patients with NPAA (Group II) between January 2016 to December 2018. Patient white blood cell (WBC) count, platelet (PLT) count, MPV, PDW, and hematocrit (HCT) were analyzed. Receiver operating characteristic (ROC) curves were used to evaluate the sensitivity and specificity of these indices in AP. Positive correlation was found between MPV and the degree of AP; as well as negative correlation between PDW and degree of AP. This is the first study to assess the MPV and PDW in pediatric patients with AP. This study showed the MPV is reduced and the PDW is normal in patients with AP. A decreased MPV value could serve as a marker to diagnose AP preoperatively. More studies are needed to establish relationship between PDW and MPV with AP. Keywords: Appendicitis perforations; Mean Platelet Volume; Platelet distribution width